Journalists' Interpretation of Press Freedom in Papua as a Conflict-Prone Region - Nahria, Nahria; Siahaan, Chontina; Nurfauziah, Isni (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2025)
Press freedom is a concept that refers to the guarantee of citizens' rights to receive information. However, the journey to realize press freedom so that it becomes an inseparable part of the order of the nation and state requires a long time with enormous challenges, especially within the conflict-prone areas. This research aims to explore press freedom in Papua, journalists' interpretation of press freedom, press freedom in reporting sensitive issues, and the causes of journalists' vulnerability to violence. It employed a case study method with a constructivist paradigm. The results showed that press freedom in journalistic activities in Papua, as a prone conflict area, has not gone well due to various obstacles. Journalists interpret freedom of the press as free from all kinds of threats, prohibitions, and intimidation, free to build relationships with anyone, and free to provide true, objective, and non-biased information as a form of responsibility to the public. Journalists interpret the press freedom guarantee in Press Law No.40 of 1999 as still needing firmness and special discussion, especially regarding journalistic activities and special protection in conflict areas as a necessity in various forms. Press freedom in reporting sensitive issues in Papua, as a prone conflict area, requires journalists to consider their safety. The causes of the vulnerability of journalists to violence in Papua Province, as a prone conflict area, are the low professionalism of journalists, the suboptimal role of press companies and journalist organizations in providing protection.